Equivalence in English – Vietnamese translation of financial terms - Phùng, Thị Hồng Anh (2021)
This research aims at finding translation equivalence and procedure applied in the translation of financial terms the book “International Economics” (nineth edition) by Krugman Obstfeld Melitz in 2011 and which of them is the most popular. Besides, the strategies to deal with the case of non – equivalence are also discussed in this study. The data were 269 financial terminologies collected from the book “International Economics” and its translation version by National Political Publishing House. Both qualitative and quantitative methods were employed in this study. The researcher used qualitative method to analyze 269 financial terms to find out types of translation equivalence and procedure applied in their translation. Quantitative method was employed to find out the highest density of translation equivalence and procedure applied in the translation of financial terms in the book. On the completion of the research, three important findings were drawn. Firstly, seven translation equivalences were applied to translate financial term in the book, namely denotative, connotative, formal, pragmatic, dynamic, one – to – many and one – to – part – of – one equivalence. Among them, denotative equivalence was the most popular one applied in the translation of financial terms. Secondly, seven translation procedures were applied to translate financial terms in the book, namely through translation, shift, modulation, couplets, functional, cultural and descriptive equivalence. Among them, through translation is the highest density procedure applied in the translation of financial terms. Thirdly, four strategies to deal with non – equivalence terms were found out, namely descriptive equivalent or couplets, loan plus explanation, paraphrase and illustration.